Halocarbon emissions by selected tropical seaweeds: species-specific and compound-specific responses under changing pH - Mithoo-Singh, Paramjeet Kaur; Keng, Fiona S.L.; Phang, Siew Moi; Leedham-Elvidge, Emma; Sturges, William T.; Malin, Gill; Abd Rahman, Noorsaadah (PeerJ, 2017)
Five tropical seaweeds, Kappaphycus alvarezii (Doty) Doty ex P.C. Silva, Padina australis Hauck, Sargassum binderi Sonder ex J. Agardh (syn. S. aquifolium (Turner) C. Agardh), Sargassum siliquosum J. Agardh and Turbinaria conoides (J. Agardh) Kützing, were incubated in seawater of pH 8.0, 7.8 (ambient), 7.6, 7.4 and 7.2, to study the effects of changing seawater pH on halocarbon emissions. Eight halocarbon species known to be emitted by seaweeds were investigated: bromoform (CHBr3), dibromomethane (CH2Br2), iodomethane (CH3I), diiodomethane (CH2I2), bromoiodomethane (CH2BrI), bromochloromethane (CH2BrCl), bromodichloromethane (CHBrCl2), and dibromochloromethane (CHBr2Cl). These very short-lived halocarbon gases are believed to contribute to stratospheric halogen concentrations if released in the tropics. It was observed that the seaweeds emit all eight halocarbons assayed, with the exception of K. alvarezii and S. binderi for CH2I2 and CH3I respectively, which were not measurable at the achievable limit of detection. The effect of pH on halocarbon emission by the seaweeds was shown to be species-specific and compound specific. The highest percentage changes in emissions for the halocarbons of interest were observed at the lower pH levels of 7.2 and 7.4 especially in Padina australis and Sargassum spp., showing that lower seawater pH causes elevated emissions of some halocarbon compounds. In general the seaweed least affected by pH change in terms of types of halocarbon emission, was P. australis. The commercially farmed seaweed K. alvarezii was very sensitive to pH change as shown by the high increases in most of the compounds in all pH levels relative to ambient. In terms of percentage decrease in maximum quantum yield of photosynthesis (Fv=Fm) prior to and after incubation, there were no significant correlations with the various pH levels tested for all seaweeds. The correlation between percentage decrease in the maximum quantum yield of photosynthesis (Fv=Fm) and halocarbon emission rates, was significant only for CH2BrCl emission by P. australis (r D0:47; p≥0:04), implying that photosynthesis may not be closely linked to halocarbon emissions by the seaweeds studied. Bromine was the largest contributor to the total mass of halogen emitted for all the seaweeds at all pH. The highest total amount of bromine emitted by K. alvarezii (an average of 98% of total mass of halogens) and the increase in the total amount of chlorine with decreasing seawater pH fuels concern for the expanding seaweed farming activities in the ASEAN region.